{Tuning the Reactivity of O - tert -ButyldimethylsilylimidazolylAminals Towards Organolithium Reagents} - Gimisis, Thanasis; Arsenyan, Pavel; Georganakis, Dimitris; Leondiadis, Leondios (Synlett, 2003)
O-tert-Butyldimethylsilylimidazolyl aminals are N,O-acetals that form readily from aldehydes, and although they function as aldehyde stabilizing and protecting groups under various conditions, we report here that they react with organolithium reagents similarly to the parent aldehydes. The mechanism involves the intermediate formation of a 2-imidazolyl anion as is exemplified by the isolation of 2-TBDMS-imidazole. Substitution of the imidazolyl moiety at the 2-position renders these aldehyde derivatives stable to organolithium reagents, thus allowing for the tuning of their reactivity.
Keywords: Brook rearrangements; N; O-acetals; Org; [Aldehydes